Nutritive value of forages us affected by soil and climatic differences; limestone pasture vs. sandstone pasture - Koch, B.A.; Smith, E.F.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
This report is a summary of the results obtained in the first trial of a study designed to determine differences in the nutritive value, for beef cattle, of forages grown on limestone or sandstone soils. Preliminary results were reported in detail in Kansas Circular 349. In a study of this sort there are many variables which cannot be completely controlled or eliminated. It is virtually impossible to select pastures and meadows that are alike in every detail. Pastures within a few miles of each other receive differing amounts of moisture in a given period of time. Previous treatment, type of forage, yield of forage; all of these and many other variables affect the results obtained. Therefore, several trials extending over a number of years must be carried out before definite conclusions can be made.
Keywords: Beef; Forage; Limestone vs. sandstone pasture; Gain